KOMUNIKASI DIGITAL DALAM KOMUNITAS TRANSPORTASI: STUDI POLA INTERAKSI ANTARA BISMANIA DAN PERUSAHAAN OTOBUS DI FACEBOOK - M Syarif Taufiq Hidayatullah; Fitria Nur ‘Aini (CV. Denasya Smart Publisher, 2025)
This study aims to examine the communication patterns formed within the Bismania community on Facebook and to explore how interactions between bus enthusiasts and bus companies (Perusahaan Otobus/PO) are constructed through social media. Employing a descriptive qualitative approach, data were collected through observation of interactions in five major Facebook groups related to Bismania and in-depth interviews with 25 informants, consisting of group administrators and active members. The analysis employed three theoretical frameworks: Uses and Gratifications to explain members’ motivations in using social media, Dialogic Communication Theory to analyze communication practices of bus companies, and Media Affordances to understand how Facebook’s technical features shape interaction dynamics. The findings indicate that the Bismania community serves not only as a space for entertainment and information exchange but also as a digital public that articulates criticism, appreciation, and advocacy toward public transportation services. However, bus companies tend to adopt a top-down communication style and have not fully implemented dialogic practices. These findings highlight the strategic role of transport-related digital fan communities in shaping public opinion, collective identity, and trust toward companies